OP0269 Activation of mertk+cd206+ subpopulation of human synovial tissue-resident macrophages limits inflammatory response. (12th June 2018) - Finlay, S.R.; Alivernini, S.; Elmesmari, A.; Tolusso, B.; Perticca, L.; Di Mario, C.; Capacci, A.; Filer, A.; Ferraccioli, G.; McInnes, I.; Gremese, E.; Kurowska-Stolarska, M.
Abstract : Background: Current therapies have transformed the management of rheumatoid arthritis. However, there are still a substantial proportion of patients who do not respond to treatments, and among those who respond, only small proportion achieve disease remission. We showed previously that human synovial tissue macrophages (STMs) are a heterogeneous population; and a sub-population of CD206 + MertK + positive STMs predominates in RA patients in sustained remission, in contrast to patients with active RA. Their surface receptors, e.g. MerTK, and distinct transcriptome suggest that they may play a pivotal role in re-enforcing joint homeostasis during remission. 1 Thus, we hypothesise that activation of CD206 + MerTK + human synovial tissue macrophages contribute to the resolution of inflammation. Objectives: We aimed to investigate whether activation of MerTK in STM sub-population promotes an anti-inflammatory environment in the synovium. Methods: Using flow cytometric techniques and with a specific antibody panel design, 1 STMs from digested RA synovial biopsies (n=36) were phenotyped and/or harvested. Patients' group included 28 patients with active disease and 8 patients in remission (DAS28 ESR <2.6 and power doppler negative). After excluding all other cell types, macrophages were gated based on the expression of CD64 and CD11b (CD45 pos CD64 pos CD11b pos HLA-DR pos ). 1 Two distinct subpopulations: CD206 + MerTK + and CD206 - MerTK - were sorted and cultured on a collagen coated 96-well plate at 1000 cells per well in the presence of with LPS (10 ng/ml)±Gas6, a MerTK ligand (200 ng/ml), for 24 hour. TNF production was measured with a high sensitivity ELISA. Results: As previously shown, 1 RA patients in sustained remission have a majority of CD206 + MerTK + STMs whilst patients with active RA show an increased number of CD206 - MerTK - macrophages. The percentage of CD206 + MerTK + macrophages negatively correlated with the disease activity score. Stimulation of FACS-Aria sorted CD206 + MerTK + and CD206 - MerTK - macrophages with TLR4 ligand induced TNF production. However, activation of MerTK pathway by Gas6 inhibited LPS-induced TNF production by CD206 + MerTK + subpopulation. Conclusions: CD206 + MERTK + macrophages, which predominate in RA patients in remission, have Gas6-mediated negative feedback mechanism limiting TNF production. Thus, Gas6/MerTK pathway in synovial tissue macrophages could drive the resolution of inflammation and synovial tissue homeostasis. Further functional and transcriptomics studies will reveal the therapeutic potential of CD206 + MERTK + macrophages. Reference: [1] Elmesmari A, et al. Synovial tissue of RA patients in remission contains a unique population of regulatory macrophages. Annals of the Rheumatic Diseases2017;76(Suppl2):138–139. Disclosure of Interest: None declared